Halal Industrial Food Waste Management: Lesson Learnt From Japan - Sulaiman, Nor Surilawana (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2023)
One-third of all food produced for human use is wasted or discarded into the environment via landfilling. Currently, the only cheaper and easier option in Brunei is landfill. Dumping organic waste materials from industrial food waste into the environment contributes to harmful environmental effects. The value of food waste is being increasingly recognised, and Brunei Darussalam is among the highest in the area, with a solid waste output of 1.4 kg per capita per day. However, just 11.3% of food waste is estimated to have been recycled, with the remainder ending up in landfills. Through participation in the JENESYS Programme, the researcher virtually visited a company at Kobe Plant. The session was eye-opening and related to responsible consumption and production where the company implemented zero waste.  In this context, this paper will highlight the waste reduction concept to enhance the current state of halal industrial food waste management. Through waste reduction or zero-waste implementation, these wastes can be converted into value-added products. This would strengthen the halal food sector and support the government's aspiration to achieve Brunei Vision 2035 Goal 3 – Dynamic and Sustainable Economy as well as SDG Goal 12 – Responsible Consumption and Production. This study also shows how effective waste reduction for a sustainable, healthy environment and circular economy may be achieved by handling industrial food waste.